2018
DOI: 10.1021/acsphotonics.8b00484
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Resonant Energy Transfer Using Optical Topological Transitions in Metamaterials

Abstract: The control and enhancement of resonance energy transfer is highly desirable for a variety of applications ranging from solar cells to spectroscopic rulers. However, the process of direct resonance energy transfer is distance dependent and limited to ∼10 nm for typical donor–acceptor pairs. Here we demonstrate long-range (∼160 nm) direct energy transfer between donor quantum dots and acceptor dye molecules through the use of an optical topological transition (OTT) in a metamaterial. The OTT in a metamaterial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…[22] Recently, some studies have also shown HMM mediated emission resonance energy transfer between molecules separated by a large distance of over 100 nm. [28][29][30] These results show the effective coupling of the emitted radiation to the HMM modes.…”
Section: Doi: 101002/adom202000368mentioning
confidence: 73%
“…[22] Recently, some studies have also shown HMM mediated emission resonance energy transfer between molecules separated by a large distance of over 100 nm. [28][29][30] These results show the effective coupling of the emitted radiation to the HMM modes.…”
Section: Doi: 101002/adom202000368mentioning
confidence: 73%
“…3a. We exploit this feature to transfer energy from TaSe 2 to other semiconducting TMDC layers using dipole-dipole coupling through NRET process [17][18][19] . Due to layered structure, the transition dipoles formed in both MoS 2 and TaSe 2 are quasi-twodimensional in nature.…”
Section: Resultsmentioning
confidence: 99%
“…We show that this material exhibits strong optical absorption and photoluminescence (PL), while maintaining metallic conductivity behavior. These properties have been explored here to demonstrate versatile device applications of 2H-TaSe 2 , for example, (1) as a donor layer for non-radiative resonant energy transfer (NRET) [17][18][19][20] to other material, (2) as an efficient hot electron injector, (3) as a contact material for planar and vertical devices, and finally (4) as a dual-purpose layer, namely as light absorber as well as photo-carrier collector, in a sensitive, high speed vertical photodetector.…”
mentioning
confidence: 99%
“…Compared with other optical metamaterials, like chiral and split ring resonator–based metamaterials, HMMs have advantages of relative ease of fabrication at optical frequencies, broadband nonresonant and 3D bulk responses, and flexible wavelength tunability. As a result, HMMs have attracted widespread interest and become a good multifunctional platform for many exotic applications, such as optical negative refraction and light beam steering, subdiffraction‐limited imaging and nanolithography, spontaneous and thermal emission engineering, ultrasensitive optical, biological, and chemical sensing, omnidirectional and broadband optical absorption …”
Section: Introductionmentioning
confidence: 99%